Response of Eleusine indica L. Gaertn towards herbicides and N fertilizer in aerobic rice system. - Gunavathy Selvarajh. (2018)
Aerobic rice systems can be an alternate way to cultivate rice in water deficiency conditions. However, weeds are the major constraints in an aerobic rice field which decline its success. To increase competitiveness with weeds and achieve the optimum growth of rice, weed management needs an integration of herbicides and optimum nitrogen (N) fertilizer rates. Hence, this study was conducted to examine the response of Eleusine indica to herbicides and N fertilizer in aerobic rice systems. The phytotoxicity of herbicide (pendimethalin, pretilachor, cyhalofop-butyl, bispyribac-sodium) and N fertilizer (urea, ammonium nitrate, ammonium sulphate) against E. indica at the different growth stage of aerobic rice (0, 4, 8, 12 day after sowing) was observed in the nursery and field-like conditions. The phytotoxicity test in the nursery condition revealed that the herbicide (pendimethalin, ED50 = 0.327 kg ai ha-1) and N fertilizer (urea, ED50 = 116-120 kg ha-1), was highly phytotoxic to E. indica where the weed emergence and shoot fresh weight was reduced by 50% at a concentration less than half from the highest application rate. Even though the weed inhibition was marked stronger at 1.0 kg ai ha-1 pendimethalin and 240 kg ha-1 urea with > 75% inhibition, urea has exerted a stimulation effect on the aerobic rice seedlings, regardless of any application rate. Meanwhile, pendimethalin has shown a slight injury on the rice seedlings where the effect was likely negligible. Pendimethalin and urea were subsequently selected, and further result demonstrated that banded application of pendimethalin and urea gave a positive response in suppressing E. indica weed. Irrespective of pendimethalin rate, the highest inhibition was exerted by urea at 240 kg ha-1 where it almost completely inhibited the germination and reduced the shoot fresh weight of E. indica with 87-90% inhibition. Reduction in root length, shoot fresh weight, shoot height and leaf greenness of the rice plants was noticeable at 0 day after sowing (DAS) across pendimethalin-urea rates and the rice plants became less susceptible with increasing growth stages. Under the field-like environment, 0.50 kg ai ha-1 pendimethalin + 240 kg ha-1 urea and 1.00 kg ai ha-1 pendimethalin + 240 kg ha-1 urea gave a significant suppression on the emergence and seedlings growth of E. indica with 60-90% inhibition. The aerobic rice growth performance was highly stimulated and the grain yield production was higher for both treatments due to lesser competition with weed. The weed suppression exerted by pendimethalin-urea might be due to inhibition of root, shoot, photosynthesis and cell division. However, 0.50 kg ai ha-1 pendimethalin + 240 kg ha-1 urea and 1.00 kg ai ha-1 pendimethalin + 240 kg ha-1 urea did not show significant stimulation in all growth parameters except for panicle length. These results imply that 0.50 kg ai ha-1 pendimethalin + 240 kg ha-1 urea can be adopted to control E. indica effectively while enhancing the growth performance of aerobic rice plants.